Exome Analysis of Patients with Concurrent Pediatric Inflammatory Bowel Disease and Autoimmune Disease. Issue 6 (June 2015) - Andreoletti, Gaia; Ashton, James J.; Coelho, Tracy; Willis, Claire; Haggarty, Rachel; Gibson, Jane; Holloway, John; Batra, Akshay; Afzal, Nadeem A.; Beattie, Robert Mark; Ennis, Sarah
Abstract : Background: Pediatric Inflammatory Bowel Disease (PIBD) is a chronic condition seen in genetically predisposed individuals. Genome-wide association studies have implicated >160 genomic loci in IBD with many genes coding for proteins in key immune pathways. This study looks at autoimmune disease burden in patients diagnosed with PIBD and interrogates exome data of a subset of patients. Methods: Patients were recruited from the Southampton Genetics of PIBD cohort. Clinical diagnosis of autoimmune disease in these individuals was ascertained from medical records. For a subset of patients with PIBD and concurrent asthma, exome data was interrogated to ascertain the burden of pathogenic variants within genes implicated in asthma. Association testing was conducted between cases and population controls using the SKAT-O test. Results: Forty-nine (28.3%) PIBD children (18.49% CD, 8.6% UC, and 21.15% IBDU patients) had a concurrent clinical diagnosis of at least one other autoimmune disorder; asthma was the most prevalent, affecting 16.2% of the PIBD cohort. Rare and common variant association testing revealed 6 significant genes ( P < 0.05) before Bonferroni adjustment. Three of these genes were previously implicated in both asthma and IBD ( ZPBP2 IL1R1, and IL18R1 ) and 3 in asthma only ( PYHIN1, IL2RB, and GSTP1 ). Conclusions: One-third of our cohort had a concurrent autoimmune condition. We observed higher incidence of asthma compared with the overall pediatric prevalence. Despite a small sample size, SKAT-O evaluated a significant burden of rare and common mutations in 6 genes. Variant burden suggests that a systemic immune dysregulation rather than organ-specific could underpin immune dysfunction for a subset of patients. Abstract : Article first published online 17 April 2015.Supplemental Digital Content is Available in the Text.